PRODUCT-SERVICE SYSTEMS AS SUSTAINABLE ALTERNATIVES TO MOBILITY: A COMPARATIVE ANALYSIS OF TWO BIKE-SHARING SYSTEMS - Sousa-Zomer, Thayla Tavares de (2016)
Product-Service Systems (PSS) have been discussed as promising business models to redirect the contemporary production and consumption patterns towards sustainability. However, the research on PSS is mostly dictated by theoretical works and more empirical investigations are needed. Additionally, empirical studies that compare PSS solutions situated in different contextual conditions are required. This paper aims at analyzing two use-oriented bike-sharing systems with sustainability potential in order to contribute to PSS empirical body of knowledge. A PSS located in a developed country and another one available in an emerging economy were selected to be investigated. A qualitative analysis was carried out considering the contextual conditions of each solution: PSS elements, sustainable business models components, and sustainability potential, based mainly on secondary data. The results confirmed that these PSS models can provide environmental, economic, and social benefits. The analysis and comparison between the solutions also demonstrated differences in both systems such as integration with other transportation modes and renewable energy usage that may affect customer acceptance and PSS sustainability performance. Customer behavior, acceptance and satisfaction need further study. Understanding the real factors that motivate customers to use a bike-sharing system in different contexts can be useful in efforts to spread its future adoption.